Evaluation of metastasis and 5-year survival in oral squamous cell carcinoma patients in Isfahan (2001-2015) - Nabet Tajmirriahi; Seyed Mohamad Razavi; Samaneh Shirani; Solmaz Homayooni; Gamezeh Gasemzadeh (Wolters Kluwer Medknow Publications, 2019)
Background: Frequency analysis of metastasis in patients with oral squamous cell carcinoma (OSCC) helps to partly anticipate the upcoming chance of metastasis in the patients following primary diagnosis. This study was conducted to determine the evaluation of metastasis and 5-year survival in OSCC. Materials and Methods: This was a retrospective, descriptive study. A total of 96 OSCC patients were studied. Demographic data and clinical view of lesion as well as histopathological grade of patients were recorded in previously prepared forms of pathology centers. These findings were then evaluated in relation to the 5-year survival. The obtained data were fed into SPSS and analyzed by Chi-square test, t-test, one-way ANOVA, and Scheffé test. A significant level of α = 0.05 was used. Results: The 5-year survival of patients was 41.7%. From among the patients, 44% were found to have local recurrence and 36% were reported to have distant metastasis. There was no significant association between the 5-year survival rate and primary grade (P = 0.105). However, it revealed a significant relationship between the 5-year survival rate and distant metastasis (P = 0. 001). Conclusion: This study showed that the 5-year survival is dependent on the primary site of involvement, local recurrence, regional and distant metastasis, and mean age. However, gender (P = 0.89), grade (P = 0.105), and stage (P = 0.242) have no effect on the 5-year survival of patients.